Borders, Identities, And Chicana Feminism: An Analysis of The Notion Of Mestizaje in Borderlands by Gloria Anzaldúa - Accossatto, Romina (Millcayac - Revista Digital de Ciencias Sociales, 2025)
In this paper, we explore the notion of mestizaje as proposed by Gloria Anzaldúa in her seminal work Borderlands/La Frontera: The New Mestiza (1987), with the aim of identifying potential contributions that this Chicana author introduced—at a very early stage—into debates intersecting the categories of class, race, gender, and sexualities. We focus particularly on three key concepts that engage with the idea of mestizaje throughout the text: the border, the border language, and Chicana identities.